Agreement between hemocue and glucose oxidase methods for blood glucose measurement in a field work study of diabetes: the Comcaac project - Gallegos-Aguilar, Ana Cristina Gallegos-Aguilar (2019)
Abstract To monitor and detect blood glucose (BG) abnormalities, health professionals use glucose meters. The study’s objective was to compare HemoCue (HC) versus glucose oxidase (GOx) for the measurement of BG using 368 measurements of BG by both methods. Bland & Altman graphs, paired t-test and linear regression were used to compare the methods. Concordance was found between the methods in most glucose levels, except at glucose concentrations ≥ 6.993 mmol / L. HC glucose analyzer is good for use in field studies because it is technically easy and requires very little maintenance; however, it is recommended to take special care with people whose glucose values are within the limit of the diagnosis of diabetes, since with the HC method there is a risk of misclassifying people who already have diabetes, as non-diabetics. Therefore, given the importance of knowing the actual values of glucose levels in this group of people for an accurate diagnosis, considering a subsequent analysis with the GOx method to corroborate the result is recommended.